Modeling support to acoustic sensing at the surface of Mars - Jacob, Xavier; Chide, Baptiste; Maurice, Sylvestre; Bertrand, Tanguy (The Journal of the Acoustical Society of America, 2023)
Acoustic propagation in the atmosphere of Mars is the subject of renewed interest since the presence of microphones on the surface of the red planet. The analysis of the recordings collected by the SuperCam microphone of the NASA Perseverance rover has already shown that the acoustic properties of Mars atmosphere do fit the existing models, and so far, the meteorological data have been available. On this basis, classical atmospheric propagation models have been adapted, including the effects of ground, temperature gradient, wind, and turbulence. A sensitivity study is presented, using two configurations that correspond to the main actual sources and propagation paths experienced on Mars : one similar to the point-like pulsed source that is generated by the expansion of the plasma of the LIBS technique, and the other analogue to the tonal low frequency noise emission of the ingenuity drone. Modeling results show to what extend this two configurations can be use to assess ground or atmospheric properties.